Composition Optimization and Field Application of Colored Emulsified Asphalt Seal Mixture - Sun, Zhilin; Zhu, Zhihang; Zhang, Junhui; Wu, Chao (Frontiers in Materials, 2020)
A uniform test design method was used to investigate the storage stability, wear resistance performance, anti-slide performance, and color durability of a colored emulsified asphalt seal mixture (CEASM). The optimal mix proportions of the seal mixture were determined, and the engineering test application and effect evaluation analysis were performed. The results show that the clay, silica fume, pigment, mineral aggregate, and emulsified asphalt contents in the prepared mixture ranged from 15–17%, 12–16%, 10–14%, 28–32%, and 25–32%, respectively. In practical engineering applications, CEASM with a molding thickness of 2–3 mm stored in liquid form has a good storage stability and wear resistance, which is suitable for manual scraping pavement or mechanical spraying construction. In addition, it has been shown that colored pavement has the advantages of low cost, safety, environmental protection, convenient construction, good durability, and rapid molding. The CEASM also has great application prospects in color repaving for non-color roads, the early maintenance of colored pavement, and road disease maintenance. The results guide colored pavement designs to improve the storage stability of CEASM and enhance the color durability and crack resistance of colored pavements.